Gene-sensor on the Basis of Magnetic Immobilization and Bioimpedance Measurements: a proof of concept. (July 2019) - Laguna, D U; Sanchez, V; Ames, G; González, C A
Abstract: Detection of molecular markers or specific DNA sequences (genes) represents the future in genomic medicine. Gene detection requires expensive equipment and specialized technicians, thus biosensors development that allows such detection quickly, economically and simply is fundamental in the first level of health care. In this study the development and evaluation of a genosensor based on magnetic anchoring of DNA sequences and electrical bioimpedance spectroscopy measurements is presented. As a first proof of concept, bioimpedance measurements were developed in PCR product anchored by magnetic nanoparticles and two conditions were compared; PCR product and absence of amplicons. The experimental evaluation indicates technical feasibility of developing a biosensor of molecular markers or specific genes trough electric bioimpedance measurements assisted with magnetic nanoparticles. The observations show that the DNA biosensor proposal offers the possibility of detecting a PCR product and differentiating it from the absence of amplicons.